A „KEGYETLENÜL SZOMORÚ KÖTELESSÉG” A TRIANONI BÉKEDIKTÁTUM BECIKKELYEZÉSE 3.: A RATIKÁCIÓS VITA A NEMZETGYŰLÉSBEN 1920. NOVEMBER 13. - Dr. Vizi, Tamás László (Közép-Európai Közlemények, 2019)
This study is a continuation of the previously published paper in the Central European Publications No. 35, and No. 43. The study is a continuation of the previously published paper in the Central European Publications No. 35, which presented the political controversies about the codifing of the Trianon Peace Treaty and that massive pressure exerted on Hungary by the great powers for the purpose of making it. The antecedents of the ratification process and the entry into force of the Peace Treaty were the result of more than one year's process. The first study describes the period from 4th June 1920, the signing of the peace treaty, till 26th October 1920, the referral of the peace treaty to the National Assembly. The second study detailed the content of the ratification bill and its justification. Described further developments regarding the ratification of the Trianon Peace Treaty, opinions of leading Hungarian politicians and the decisions of the National Assembly Committee, which determined Hungarian political life and influenced the daily life of the public until the commencement of the National Assembly ratification debate. This study continues the previous one and presents the details of the ratification debate, on 13 November 1920. Details the pre-debate press news, the expectations of the public, statements by the chairmen of the National Assembly Committees. Than it describes and analyzes the detailed discussion, the arguments of the opposing politicians who did not support ratification. These speeches point to the fatal flaws of the peace treaty, the measures that have befallen the Hungarians for a century in its brutality.